KEBIJAKAN PENGEMBANGAN PARIWISATA BERKELANJUTAN: KAJIAN TEORETIS DAN EMPIRIS - Sri Widari, Dewa Ayu Diyah (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2020)
The importance of the role of tourism industry for the economy encourages a country to develop the tourism sector, but also face challenges in its development. This research aims to assess the policy of sustainable development and the implementation of sustainability tourism policy of economic, socio-cultural, and environmental aspects. The method of collecting data through document study. Changes in travelers’ pattern, changes of travelers’ psychography influence the tourism development model. Sustainable tourism development is an effort to be able to face global and national competitions. Tourism policy plays an important role in the development of sustainable tourism, its implementation depending on the support of the central government, local government, industry, and the community. While sustainable tourism is important, economic growth is still a vital aspect of the government in some developing countries.